Navigating Complexity: Political Education in a Global Challenge - Andriyanti, Septimia; Patmisari, Patmisari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to determine the effect of political education on the po-litical participation of novice voters in the era of globalization challenges. Methodology: This study uses a correlational method with a quantitative focus. The popula-tion in this study was 8,831 students, and the sample was 243 stu-dents who received a questionnaire with 50 statement items. Data collection techniques used questionnaires, and validity and reliability tests were carried out. This study uses data analysis techniques, and prerequisite test analysis, namely normality test, multicollinearity test, heteroscedasticity test, and hypothe-sis testing, namely simple regression test, T-test, and coefficient of determination. Results: The results showed that political education has a positive and partially signif-icant effect on the political participation of novice voters in the 2024 elec-tions, with a t-count of 7.890 greater than the t-table of 1.970. Political edu-cation affects the level and quality of political participation of novice voters. Political education must be carried out sustainably and involve various par-ties, such as educational institutions, mass media, and civil society organiza-tions. Political education is critical to answering current global challenges be-cause political ed-ucation is the main tool to increase citizens' awareness and capacity to partici-pate in solving global problems. Applications/Originality/Value: Global aspects, theoretically, at the formal level, schools can build a curricu-lum that integrates an understanding of global politics through teaching Pan-casila; at the community level, political education programs can be imple-mented through public discussions, digital platforms, and social media.